PARTISIPASI MASYARAKAT DALAM MENGELOLA OBJEK WISATA HUTAN BAMBU DI DESA SUMBERMUJUR KECAMATAN CANDIPURO - Yudistira, Dickky Divani Tri; Margono, Margono; Shofa, Abd.Mu’id Aris (JURNAL MASTER PARIWISATA, 2023)
The purpose of this study was to find out about the process of creating tourist attractions, community participation in the process of managing the Bamboo Forest Tourism Object and the economic impact felt by the community after the opening of the Bamboo Forest Tourism Object. This research uses a qualitative research approach with a descriptive type. Sources of research data obtained through informants, events, and documents. Data collection procedures were carried out through observation, interviews, and documentation. Data analysis used Miles and Huberman's interactive model through the stages of data collection, data reduction, and data presentation, as well as drawing conclusions. The results showed that the process of creating the Bamboo Forest Tourism Object was due to the participation of the people of Sumbermujur Village through the Semeru Belt Pokdarwis. The forms of participation of the Sumbermujur Village community in managing tourism objects can be seen through their participation in the form of thought participation, property participation, labor participation, skill participation and social participation. The perceived economic impact is the increase in the income of the people of Sumbermujur Village through trading activities and the service sector around tourist sites. Keywords: bamboo forest; community participation; tourism management.